2024
DOI: 10.1101/2024.02.11.579819
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phages reconstitute NAD+to counter bacterial immunity

Ilya Osterman,
Hadar Samra,
Francois Rousset
et al.

Abstract: Bacteria defend against phage infection via a variety of antiphage defense systems. Many defense systems were recently shown to deplete cellular nicotinamide adenine dinucleotide (NAD+) in response to infection, by breaking NAD+to ADP-ribose (ADPR) and nicotinamide. It was demonstrated that NAD+depletion during infection deprives the phage from this essential molecule and impedes phage replication. Here we show that a substantial fraction of phages possess enzymatic pathways allowing reconstitution of NAD+from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Based on homology, we initially assumed NrsA was a phosphoribosyl pyrophosphate synthetase, converting ribose 5-phosphate to phosphoribosyl pyrophosphate, and NrsB, a nicotinate phosphoribosyl transferase that adds nicotinic acid to phosphoribosyl pyrophosphate to generate nicotinic acid mononucleotide (34). However, during the preparation of this manuscript, a biochemical characterization of proteins highly homologous to NrsAB was deposited in bioRxiv (35). The authors reported that homologs of In summary, we establish that the classical biotype V. cholerae encodes two phage defensive systems, Gabija and Nezha, absent from El Tor biotype strains.…”
Section: Discussionmentioning
confidence: 99%
“…Based on homology, we initially assumed NrsA was a phosphoribosyl pyrophosphate synthetase, converting ribose 5-phosphate to phosphoribosyl pyrophosphate, and NrsB, a nicotinate phosphoribosyl transferase that adds nicotinic acid to phosphoribosyl pyrophosphate to generate nicotinic acid mononucleotide (34). However, during the preparation of this manuscript, a biochemical characterization of proteins highly homologous to NrsAB was deposited in bioRxiv (35). The authors reported that homologs of In summary, we establish that the classical biotype V. cholerae encodes two phage defensive systems, Gabija and Nezha, absent from El Tor biotype strains.…”
Section: Discussionmentioning
confidence: 99%